Entre os documentos e as retomadas : movimentos da luta pelo território em Brejo dos Crioulos (MG) - Costa, Pedro Henrique Mourthé de Araújo (2015)
It has been seventeen years of struggle since the opening of the legal procedures for the recognition of Brejo dos Crioulos - a community located in the Outback North Miner, on the border of three cities - São João da Ponte, Verdelâ ndia and Varzelâ ndia -, as a “quilombo remnant territory”. Victims of a violent territorial expropriation process since the mid-1930s, the quilombolas started retaking their territory in 1998, with confrontations inside and outside the quilombo with the aim of pushing forward the process of land titling. Due to the slowness of the State in dispossessing the farmers who have ocupied the region ilegally, the quilombolas haved used two strategies in their confrontations: the retomadas [land retaking] and the mobilization of a partners network and of documents - legal proceedings, reports, anthropological report, decrees, correspondence, notes, projects, inquiries and police inquiries - in different institutions and in various courts, featuring a bureaucratic universe that is actuated at various moment. This landscape of conflict is composed by an interweaving of various political forces. This dissertation deals with the various movements that make up the struggle for the territory in Brejo dos Crioulos, which was only recognized as a “quilombo remnant” by the Palmares Cultural Foundation (FCP) in 2004, by describing ethnographic encounters between the quilombolas, anthropology and State in the course of the titling process.